TOWARD THE DESIGN OF VILLAGE INFORMATION SYSTEMS AS A VILLAGER COMMUNICATION MEDIUM - TOPAN SETIAWAN; DWININGTYAS PADMANINGRUM (CV KULTURA DIGITAL MEDIA, 2020)
Technology and bureaucracy are relations of systems and products of scientific knowledge. Village bureaucracy in the current reality is bureaucracy that relies on the concept of good corporate governance. The role of technology in this case is its power in forming a system that is compatible with village conditions. This article will examine how the Village Information System was designed and the extent of its contribution as a vehicle for communication. In this context it is certainly related to the development of village communities. This article is a literature review with secondary data sources including scientific publications, scientific documents and other artifacts. The result of the study is that the Village Information System provides a good communication function for stakeholder two-way communication with village communities. The geographical profile of villages in Indonesia is not all connected to the internet, so the design of SID ( Sistem Informasi Desa- Village Information System ) limited. It needs equitable development of communication - information infrastructure in Indonesia.